Pengaruh Gaya Hidup Hedonisme Terhadap Motivasi Belajar Mahasiswa Bidikmisi di Surakarta - Amir, Lutfia Nadhif Ulfa; Susilo, Agus Tri; Dewantoro, Adi (Universitas Sebelas Maret, 2023)
This study aims to (1) Describe the hedonism lifestyle profile, (2) Describe the learning motivation profile, (3) Describe the difference in hedonism lifestyle of male students and female students, (4) Describe the difference in the hedonism lifestyle of soshum students with saintek (5) Analyze the influence between hedonism lifestyle on the learning motivation of aiming students at Surakarta. The data collection techniques used in this study were questionnaires and documentation. Data analysis used descriptive analysis, Independent Sample T-test, simple linear regression analysis using a summary model, and simple correlation analysis. The results of this study showed that: (1) The majority of students aiming at FKIP UNS Class of 2017 had a low hedonism lifestyle (70.9%); (2) The majority of students have moderate learning motivation (64%); (3) There is no significant difference between the hedonistic lifestyle of male students and female students; (4) There is no significant difference between the hedonistic lifestyle of scientific students and social studies students; (5) There is a significant negative correlation between hedonism lifestyle on learning motivation with a significance value of 0.000 < 0.05 and a correlation coefficient value of (-0.497). The increase in a hedonism lifestyle is accompanied by decreased learning motivation. Vice versa, the decline in hedonism lifestyle is accompanied by increased learning motivation.